Optical antenna effect on SiNWs/CuS photodiodes - Yenchalwar, Sandeep G.; Rondiya, Sachin R.; Shinde, Pravin N.; Jadkar, Sandesh R.; Shelke, M. V. (Physica Status Solidi A-Applications and Materials Science, 2017)
One-dimensional architectures between silicon nanowires (SiNWs) and CuS were fabricated by radio-frequency (RF) magnetron sputtering and analyzed for solid-state photodetector application. Inspired by the subwavelength optical concentration by the surface plasmons on metal nanostructures at the nanoscale, we investigated the effect of gold nanorods (AuNRs) on the optical absorption and photodetection properties of the heterojunction photodiode. AuNRs acting as an optical trapping antenna enhances the light absorption, consequently boosting the photocurrent from the device. A maximum photoresponsivity of 0.36 mA W-1 was achieved under 665 nm excitation wavelength independent of the bias, a value similar to 13 times higher than for the heterojunction photodiode without AuNRs. Such plasmonic sensitization can be useful for improving the sensitivity of visible as well as IR photodetectors. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim

Uncovering the origin of enhanced field emission properties of rGO-MnO(2)heterostructures: a synergistic experimental and computational investigation - Rondiya, Sachin R.; Karbhal, Indrapal; Jadhav, Chandradip D.; Nasane, Mamta P.; Davies, Thomas E.; Shelke, V. Manjusha; Jadkar, Sandesh R.; Chavan, Padmakar G.; Dzade, Nelson Y. (RSC Advances, 2020)
The unique structural merits of heterostructured nanomaterials including the electronic interaction, interfacial bonding and synergistic effects make them attractive for fabricating highly efficient optoelectronic devices. Herein, we report the synthesis of MnO(2)nanorods and a rGO/MnO(2)nano-heterostructure using low-cost hydrothermal and modified Hummers' methods, respectively. Detailed characterization and confirmation of the structural and morphological properties are doneviaX-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Compared to the isolated MnO(2)nanorods, the rGO/MnO(2)nano-heterostructure exhibits impressive field emission (FE) performance in terms of the low turn-on field of 1.4 V mu m(-1)for an emission current density of 10 mu A cm(-2)and a high current density of 600 mu A cm(-2)at a relatively very low applied electric field of 3.1 V mu m(-1). The isolated MnO(2)nanorods display a high turn-on field of 7.1 for an emission current density of 10 mu A cm(-2)and a low current density of 221 mu A cm(-2)at an applied field of 8.1 V mu m(-1). Besides the superior FE characteristics of the rGO/MnO(2)nano-heterostructure, the emission current remains quite stable over the continuous 2 h period of measurement. The improvement of the FE characteristics of the rGO/MnO(2)nano-heterostructure can be ascribed to the nanometric features and the lower work function (6.01 and 6.12 eV for the rGO with 8% and 16% oxygen content) compared to the isolated alpha-MnO2(100) surface (phi= 7.22 eV) as predicted from complementary first-principles electronic structure calculations based on density functional theory (DFT) methods. These results suggest that an appropriate coupling of rGO with MnO(2)nanorods would have a synergistic effect of lowering the electronic work function, resulting in a beneficial tuning of the FE characteristics.

Interface-centric strategies in kesterite solar cells: addressing challenges, solutions, and future directions for efficient solar-harvesting technologies - Jagadish, Kusuma; Rahane, Ganesh K.; Kumar, Boddeda Sai; Borkar, Durgesh R.; Chordiya, Kalyani; Kavanagh, Sean R.; Roy, Anurag; Debnath, Tushar; Kolekar, Sadhu; Kahaly, Mousumi Upadhyay; Mali, Sawanta S.; Pal, Shovon; et al. (SMALL, 2024)
Keywords: band engineering; Defects; interface loss mechanism; kesterites; recombination control; solar energy

Lead-free Cs2AgBiCl6 double perovskite: experimental and theoretical insights into the self-trapping for optoelectronic applications - Rahane, Swati N.; Rahane, Ganesh K.; Mandal, Animesh; Jadhav, Yogesh; Godha, Akshat; Rokade, Avinash; Shah, Shruti; Hase, Yogesh; Waghmare, Ashish; Saykar, Nilesh G.; Roy, Anurag; Salgaonkar, Kranti N.; et al. (ACS Physical Chemistry Au, 2024)
Lead-free double perovskites (DPs) will emerge as viable and environmentally safe substitutes for Pb-halide perovskites, demonstrating stability and nontoxicity if their optoelectronic property is greatly improved. Doping has been experimentally validated as a powerful tool for enhancing optoelectronic properties and concurrently reducing the defect state density in DP materials. Fundamental understanding of the optical properties of DPs, particularly the self-trapped exciton (STEs) dynamics, plays a critical role in a range of optoelectronic applications. Our study investigates how Fe doping influences the structural and optical properties of Cs2AgBiCl6 DPs by understanding their STEs dynamics, which is currently lacking in the literature. A combined experimental–computational approach is employed to investigate the optoelectronic properties of pure and doped Cs2AgBiCl6 (Fe–Cs2AgBiCl6) perovskites. Successful incorporation of Fe3+ ions is confirmed by X-ray diffraction and Raman spectroscopy. Moreover, the Fe–Cs2AgBiCl6 DPs exhibit strong absorption from below 400 nm up to 700 nm, indicating sub-band gap state transitions originating from surface defects. Photoluminescence (PL) analysis demonstrates a significant enhancement in the PL intensity, attributed to an increased radiative recombination rate and higher STE density. The radiative kinetics and average lifetime are investigated by the time-resolved PL (TRPL) method; in addition, temperature-dependent PL measurements provide valuable insights into activation energy and exciton–phonon coupling strength. Our findings will not only deepen our understanding of charge carrier dynamics associated with STEs but also pave the way for the design of some promising perovskite materials for use in optoelectronics and photocatalysis.